2020
DOI: 10.3390/metabo10040153
|View full text |Cite
|
Sign up to set email alerts
|

Green Nut Oil or DHA Supplementation Restored Decreased Distribution Levels of DHA Containing Phosphatidylcholines in the Brain of a Mouse Model of Dementia

Abstract: Dementia is a major public health concern nowadays. Reduced levels of brain docosahexaenoic acid (DHA) and DHA-phosphatidylcholines (DHA-PCs) in dementia patients were reported previously. Recently, we have reported that supplementation of green nut oil (GNO) or DHA improves memory function and distribution levels of brain DHA in senescence accelerated mice P8 (SAMP8). GNO is extracted from Plukenetia volubilis seeds, and SAMP8 is a well-known model mouse of dementia. In this current study, we examined the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Several studies have demonstrated the relationship between brain DHA levels and events that occur with increased age. For example, patients with dementia have decreased brain DHA [27,33], and DHA supplementation improves the accumulation of brain DHA in a dementia mouse model [34,35]. Further, higher DHA intake is inversely correlated with the relative risk of AD [36].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the relationship between brain DHA levels and events that occur with increased age. For example, patients with dementia have decreased brain DHA [27,33], and DHA supplementation improves the accumulation of brain DHA in a dementia mouse model [34,35]. Further, higher DHA intake is inversely correlated with the relative risk of AD [36].…”
Section: Discussionmentioning
confidence: 99%
“…The DESI-IMS mass spectra were calibrated externally using a 500 µM sodium formate solution in 90% 2-propanol, prior to measurement. To obtain the maximum signal intensity from heart biopsy samples, DESI parameters were optimized as previously described [ 9 ] with slight modifications. All the candidate molecules corresponding to each targeted m/z were selected using the Human Metabolome Database ( https://hmdb.ca/ ) based on their mass accuracy and biological distribution.…”
Section: Methodsmentioning
confidence: 99%
“…The DESI-IMS mass spectra were calibrated externally using a 500 µM sodium formate solution in 90% 2-propanol, prior to measurement. To obtain the maximum signal intensity from heart biopsy samples, DESI parameters were optimized as previously described [9] with slight modi cations. All the candidate molecules corresponding to each targeted m/z were selected using the Human Metabolome Database (https://hmdb.ca/) based on their mass accuracy and biological distribution.…”
Section: Desi-imsmentioning
confidence: 99%